2006
DOI: 10.1073/pnas.0600048103
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of autoinhibited c-Met kinase produced by coexpression in bacteria with phosphatase

Abstract: Protein kinases are a large family of cell signaling mediators undergoing intensive research to identify inhibitors or modulators useful for medicine. As one strategy, small-molecule compounds that bind the active site with high affinity can be used to inhibit the enzyme activity. X-ray crystallography is a powerful method to reveal the structures of the kinase active sites, and thus aid in the design of high-affinity, selective inhibitors. However, a limitation still exists in the ability to produce purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 49 publications
(55 reference statements)
2
83
0
Order By: Relevance
“…D1228N, Y1230C, Y1230H, and Y1230D have all been found in hereditary or sporadic PRCC (28,29), and Y1230C has also been reported in metastases of head and neck cancer (30,31). In a recently published crystal structure of the autoinhibited, completely dephosphorylated kinase domain of MET, both D1228 and Y1230 were found to be involved in interactions that stabilize the inactive conformation, providing an explanation why mutations of these residues are selected for to enhance kinase activity (32). Because of their activating nature, some of the NVP-BVU972 resistance mutations might thus confer a selective advantage even in the absence of inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…D1228N, Y1230C, Y1230H, and Y1230D have all been found in hereditary or sporadic PRCC (28,29), and Y1230C has also been reported in metastases of head and neck cancer (30,31). In a recently published crystal structure of the autoinhibited, completely dephosphorylated kinase domain of MET, both D1228 and Y1230 were found to be involved in interactions that stabilize the inactive conformation, providing an explanation why mutations of these residues are selected for to enhance kinase activity (32). Because of their activating nature, some of the NVP-BVU972 resistance mutations might thus confer a selective advantage even in the absence of inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the binding modes of MK-2461 to c-Met and to FGFR2 may contribute to the observation that MK-2461 exhibits more potent antiproliferative activity in FGFR2-driven cells than in c-Metdriven cells, despite in vitro kinase assays showing that MK-2461 is more potent against c-Met than against FGFR2. Structural studies of several unactivated tyrosine kinases revealed that parts of the activation loop and/or other structural elements assume configurations that border or block the ATP binding site (40)(41)(42)(43). Therefore, the unactivated conformation may have significantly lower affinity for ATP than does the active conformation (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The activation loops of ALK (anaplastic lymphoma kinase) and Met also contain three tyrosines in the same positions, but lack the aspartic acid preceding the second tyrosine (a key residue in stabilizing the pseudosubstrate conformation of InsR [Till et al 2001]), and their conformations in the unphosphorylated state differ (Wang et al 2006;Lee et al 2010). In the presence of cellular (millimolar) concentrations of Mg-ATP, the unphosphorylated activation loop probably adopts multiple conformations, including the pseudosubstrate conformation, as well as conformations in which Mg-ATP is bound and the active site is available for transphosphorylation of a tyrosine from the neighboring kinase domain.…”
Section: Sr Hubbardmentioning
confidence: 99%